Short-Term Institutions, Analyst Recommendations, and Mispricing: The Role of Higher Order Beliefs - Martijn Cremers; Ankur Pareek; Zacharias Sautner (Journal of Accounting Research, 2021)
We document that stocks that have optimistic (pessimistic) consensus recommendations and are currently held by many short-term institutions exhibit large stock-return reversals: Their large past outperformance (underperformance) is followed by large negative (positive) future alphas. The predictable return reversals originate from overreaction to past recommendation releases and the correction of these overreactions around future releases. Results are stronger when earnings news is released and at firms with higher fundamental uncertainty. Further, firms with more short-term institutions show stronger announcement returns and price drift after recommendation changes. Our results are consistent with models of higher order beliefs where short-term institutions coordinate trading around public signals.
Keywords: 650; short-term institutions; analyst recommendations; mispricing; higher order beliefs